Personalization of Academic Interests: The Impact of Differentiated Smart Flipbook on Motivation and Concept Mastery in Reproductive System Learning - Rini Prihestiyani; Ellianawati Ellianawati (Institut Agama Islam Daruttaqwa Gresik, 2026)
Learning the human reproductive system in secondary schools is often hampered by the abstraction of complex biological concepts and by psychological barriers that conventional methods do not accommodate. This study aims to test the effectiveness of Differentiated Smart Flipbook media integrated with an AI Chatbot in improving concept mastery and motivation, and to investigate its inclusiveness for students with different academic interest profiles, namely Science and Sports. Using a Quasi-Experiment design with a Nonequivalent Control Group Design pattern, the study involved 113 ninth-grade students of MTs Negeri 3 Grobogan. The results of statistical tests showed that the experimental class achieved an N-Gain increase of 0.70 (high category), significantly higher than the control class, which achieved only 0.21. The most crucial finding was that this media successfully minimized the achievement gap; students interested in Sports accelerated their learning with an N-Gain of 0.67, closely following Science students (0.72). In-depth analysis reveals the operation of the Dual Coding mechanism: the AI Chatbot feature effectively facilitates Science students’ analytical skills (C4) through in-depth inquiry. At the same time, 3D visualization strengthens Sports students’ application skills (C3) through physical contextualization. It is concluded that AI-based content personalization effectively reduces cognitive load and significantly increases motivation, especially in the Relevance and Confidence aspects, making this medium an adaptive solution for realizing inclusive and equitable biology learning.